Cellulose nanofibers reinforced sodium alginate-polyvinyl alcohol hydrogels: Core-shell structure formation and property characterization. (20th August 2016) - Yue, Yiying; Han, Jingquan; Han, Guangping; French, Alfred D.; Qi, Yadong; Wu, Qinglin
Highlights: Core-shell structured hydrogels were prepared and CNFs were incorporated into the hydrogel system. The shell was micro-porous and the core was macro-porous. The hydrogels could be used in multiple adsorption–desorption cycles. The mechanical strength and adsorption capacity of hydrogel was modified by incorporating cellulose nanofibers. Graphical abstract: Abstract: Core-shell structured hydrogels consisting of a flexible interpenetrating polymer network (IPN) core and a rigid semi-IPN shell were prepared through chemical crosslinking of polyvinyl alcohol (PVA) and sodium alginate (SA) with Ca 2+ and glutaraldehyde. Short cellulose nanofibers (CNFs) extracted from energycane bagasse were incorporated in the hydrogel. The shell was micro-porous and the core was macro-porous. The hydrogels could be used in multiple adsorption–desorption cycles for dyes, and the maximum methyl blue adsorption capacity had a 10% increase after incorporating CNFs. The homogeneous distribution of CNFs in PVA-SA matrix generated additional hydrogen bonds among the polymer molecular chains, resulting in enhanced density, viscoelasticity, and mechanical strength for the hydrogel. Specifically, the compressive strength of the hydrogel reached 79.5 kPa, 3.2 times higher than that of the neat hydrogel.